(untitled) (Experimental biology, 2015)
Nematodes with the location in the digestive tract (Oswaldocruzia filiformis) reached the maximal sizes usually in fair frogs, minimal sizes – always in the frogs with intensive pigmentation. In 2008-2009 years with relatively low quantity of Rhabdias bufonis these nematodes reached the maximal sizes in fair frogs, but in 2010 year, with comparable rising of infective indicators, - in the dark amphibians (with the minimal sizes in fair-colour hosts). It is probably, that small quantity of the blood-feeding nematode (which is more energetic expensed for the frogs’ organism in comparison of gastrointestinal parasites) leaded to the minimal sizes in fair-colour hosts with their more economic metabolism, whereas in the case of the increasing of infection intensity the semi-populations of helminthes in the dark amphibians – with more intensive metabolism and, consequently, possibility of quick restoration of energetic expenditure from the blood-feeding of parasites – got the advantages.